The Influence of Problem Characteristics, Regulatory and Non-Regulatory Supporting Capabilities on The Process of Implementing E-Learning Online Learning Policies at Nusa Cendana University - LY, Piter; DJAHA, Ajis Salim Adang; DJANI, William (Journal of Tourism Economics and Policy, 2023)
This research aims to analyze the influence of problem characteristic factors, regulatory and non-regulatory carrying capacity on the implementation process of e-learning based online learning policies at Nusa Cendana University. This type of research uses a positivism paradigm with a quantitative approach, where to obtain the truth of the data, direct interviews are conducted with the object under study. The sample used in this research was 467 people who were lecturers and students at Nusa Cendana University. Research data was analyzed using descriptive statistical tests and PLS-SEM inferential statistics. The results obtained show that descriptively the four variables received a good category response with indicators of problem characteristic factors reaching 73.28%, regulatory carrying capacity of 78.27%, non-regulatory carrying capacity of 77.11% and the e-learning implementation process of 75.05%. Hypothesis testing shows that the problem characteristic factor has a significant positive influence (p<0.05) directly at 18.4% and through non-regulatory carrying capacity at 48.3% but through regulatory carrying capacity at only 5.3% it does not have a significant influence (p>0.05) towards the process of implementing e-learning based online learning policies at Nusa Cendana University. The results of the determinant test show that the problem characteristic factors have a significant moderate/moderate influence (p<0.05) through regulatory carrying capacity of 50.2% and through non-regulatory carrying capacity of 53.0% but together/simultaneously they give a strong influence of 75.3% while 24.7% was influenced by other factors outside this research.